Automatic Mesh and Shader Level of Detail - Liang, Yuzhi (IEEE transactions on visualization and computer graphics, 2023)
The level of detail (LOD) technique has been widely exploited as a key rendering optimization in many graphics applications. Numerous approaches have been proposed to automatically generate different kinds of LODs, such as geometric LOD or shader LOD. However, none of them have considered simplifying the geometry and shader at the same time. In this paper, we explore the observation that simplifications of geometric and shading details can be combined to provide a greater variety of tradeoffs between performance and quality. We present a new discrete multiresolution representation of objects, which consists of mesh and shader LODs. Each level of the representation could contain both simplified representations of shader and mesh. To create such LODs, we propose two automatic algorithms that pursue the best simplifications of meshes and shaders at adaptively selected distances. The results show that our mesh and shader LOD achieves better performance-quality tradeoffs than prior LOD representations, such as those that only consider simplified meshes or shaders